2010
DOI: 10.2169/internalmedicine.49.3760
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Tuberculous Peritonitis in a Hemodialysis Patient with High Serum Soluble Interleukin-2 Receptor and CA-125 Levels

Abstract: A hemodialysis patient with tuberculous peritonitis with hypercalcemia and high serum soluble interleukin-2 receptor (sIL-2R) and CA-125 levels is reported. An 82-year-old woman who had been on hemodialysis therapy for 6 years was admitted to our hospital for evaluation and treatment of hypercalcemia. Laboratory examination and radiologic studies revealed markedly increased serum sIL-2R and CA-125 levels and exudative ascites, with high levels of adenosine deaminase (ADA) and CA-125, which was suggestive of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…3,9 Another mechanism implicated in calcium and PTH disorders in patients with pulmonary TB involves cellular inflammatory response and immune mediators that suppress the parathyroid gland. 10,11 Some TB patients experience abnormal regulation of 1,25(OH2)D 3 with spontaneous production of the vitamin D metabolite by alveolar macrophages, contributing to hypercalcemia. 12 In vitro studies have shown that vitamin D metabolites play an important role in regulating the ability of macrophages to inhibit mycobacterial growth and influence granulomatous reactions.…”
Section: Discussionmentioning
confidence: 99%
“…3,9 Another mechanism implicated in calcium and PTH disorders in patients with pulmonary TB involves cellular inflammatory response and immune mediators that suppress the parathyroid gland. 10,11 Some TB patients experience abnormal regulation of 1,25(OH2)D 3 with spontaneous production of the vitamin D metabolite by alveolar macrophages, contributing to hypercalcemia. 12 In vitro studies have shown that vitamin D metabolites play an important role in regulating the ability of macrophages to inhibit mycobacterial growth and influence granulomatous reactions.…”
Section: Discussionmentioning
confidence: 99%
“…A predominance of neutrophils was more common in peritoneal dialysate (n=13). Four cases reported development of hypercalcemia (Lee et al, 2002;Wang et al, 2005;Borrajo et al, 2009;Kuno et al, 2010), with three cases on HD, one case on peritoneal dialysis (PD). The condition improved with normalization of hypercalcemia after the anti-TB treatment.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Increased TB incidence is also seen in dialysis patients (Pradhan et al, 1974;Ates et al, 2010). Because of cellular immunity defects, patients with end-stage renal disease (ESRD) are at increased risk of developing TB (El-Shahawy et al, 1994;Lui et al, 2001;Kuno et al, 2010). The incidence of TB in dialysis patients is 6-16 times higher than that in the general population (Kuo et al, 2001;Verettas et al, 2006;Borrajo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although serum soluble interleukin-2 receptor (sIL-2R) is often used as a biomarker in the clinical management of malignant lymphoma [5,6] and hemophagocytic syndrome [7], its levels also increase non-specifically in a variety of diseases [8,9]. However, other than hematologic malignancies, very high sIL-2R levels (e.g., more than 5,000 U/mL) occur in several conditions; namely, specific infections, several autoimmune diseases, and during organ transplant rejection [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A case study reported that high serum sIL-2R levels were useful to monitor the response to anti-tuberculosis treatment for tuberculous peritonitis in a hemodialysis patient without malignancy [17]. However, it is unknown what cut-off values of serum sIL-2R are helpful in the diagnosis of tuberculous peritonitis in patients with active hematologic malignancies, since serum sIL-2R levels are often highly elevated in hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%